An Effective Solar Photovoltaic Module Parameter Estimation Technique for Single-Diode Model. Issue 1 (September 2020) - Premkumar, M; Sowmya, R; Umashankar, S; Pradeep, J
Abstract: This paper presents a simplified parameter estimation procedure for a photovoltaic (PV) single diode model (SDM). Based on an iterative method, the module parameters are estimated for the SDM using the information from the datasheet. The five parameters of the SDM are estimated based on the datasheet using two steps. In the first step, the best ideality factor, n, value is determined, and in the next step, the value of the shunt resistance, R sh, can be calculated to increase its accuracy. For validating the performance of the estimated parameters, a model that considers the difference in the solar irradiance and the temperature. In the standard testing conditions (STC), the proposed procedure shows the best results relative to other methods. The optimization of the parameters, such as n, R sh, and series resistance, R s e, allows the minimum error between the values obtained from the proposed technique and datasheet.